Photo Rechargeable Li‐Ion Batteries Using Nanorod Heterostructure Electrodes. Issue 51 (16th November 2021) - Kumar, Amar; Thakur, Pallavi; Sharma, Rahul; Puthirath, Anand B.; Ajayan, Pulickel M.; Narayanan, Tharangattu N.
Abstract: New ways of directly using solar energy to charge electrochemical energy storage devices such as batteries would lead to exciting developments in energy technologies. Here, a two‐electrode photo rechargeable Li‐ion battery is demonstrated using nanorod of type II semiconductor heterostructures with in‐plane domains of crystalline MoS2 and amorphous MoO x . The staggered energy band alignment of MoS2 and MoO x limits the electron holes recombination and causes holes to be retained in the Li intercalated MoS2 electrode. The holes generated in the MoS2 pushes the intercalated Li‐ions and hence charge the battery. Low band gap, high efficiency photo‐conversion and efficient electron–hole separation help the battery to fully charge within a few hours using solar light. The proposed concept and materials can enable next generation stable photo‐rechargeable battery electrodes, in contrast to the reported materials. Abstract : The working (photo charging) of single nanorod (NR) containing a MoS2 /MoO x heterostructure based two‐electrode photo rechargeable battery. A high‐resolution high angle annual dark‐field image of the NR is also shown indicating the structure containing both amorphous (MoO x ) and crystalline (MoS2 ) regions.